Obsessive Jealousy: A Case Report - Perestrelo, JM (2017)
Background: Jealousy is common between humans but can assume pathological characteristics. Aims: To report a case of obsessive jealousy and to review the concept and clinical features of the condition. Methods: A clinical cases of obsessive jealousy was obtained and a literature review of the theme was shortly surveyed. Results and Conclusions: The clinical case presents a man with morbid jealousy with obsessive features who was hospitalized after a suicide attempted. During his hospitalization he was medicated with fluvoxamine and clonazepam reporting a decrease of the ruminative thoughts and anxiety. A correct diagnosis of obsessive-compulsive disorder (OCD) and its differentiation from a delusion, obsessive or overvalued idea are essential for an adequate approach and treatment.